The expression (4c − 3d)(3c + d) is equivalent to:
A. 12c2 − 13cd − 3d2
B. 12c2 − 13cd + 3d2
C. 12c2 − 05cd − 3d2
D. 12c2 − 05cd + 3d2
E. 12c2 − 03d2

Respuesta :

(4c - 3d)(3c + d) =

= 12c² + 4cd - 9cd - 3d² =

= 12c² - 5cd - 3d²

fichoh

The expression (4c − 3d)(3c + d) is equivalent to 12c² - 5cd - 3d²

(4c − 3d)(3c + d)

Open the bracket

12c² + 4cd - 9cd - 3d²

Collect like terms

12c² - 5cd - 3d²

Hence, the equivalent value of the expression is : 12c² - 5cd - 3d²

Learn more : https://brainly.com/question/18109354

ACCESS MORE